Made to stick : why some ideas survive and others die - Heath, Chip (Random House, 2008)
Urban legends, conspiracy theories, and bogus public-health scares circulate effortlessly. Meanwhile, people with important ideas--business people, teachers, politicians, journalists, and others--struggle to make their ideas "stick." Why do some ideas thrive while others die? And how do we improve the chances of worthy ideas? Educators and idea collectors Chip and Dan Heath reveal the anatomy of ideas that stick and explain ways to make ideas stickier, such as applying the "human scale principle," using the "Velcro Theory of Memory," and creating "curiosity gaps." In this fast-paced tour of success stories (and failures), we discover that sticky messages of all kinds--from the infamous "kidney theft ring" hoax to a coach's lessons on sportsmanship to a vision for a new product at Sony--draw their power from the same six traits. This book that will transform the way you communicate ideas.--From publisher description.